2018
DOI: 10.18203/2394-6040.ijcmph20183976
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of risk of fall in elderly people in the urban field practice area of Community Medicine Department, Andhra Medical College, Visakhapatnam, Andhra Pradesh

Abstract: Background: More than 1/3rd of older adults fall each year and 10-20% of falls cause serious injuries. Vast majority of these falls (>99.9%) are unintentional. This research is focused to identify prevalence of the risk of fall among elderly and  associated factors were assessed in the present study. We are going assess the risk of falls and associated factors among elderly.Methods: A cross-sectional study conducted in urban field practice area of Community Medicine Department, Andhra Medical College among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
1
2
1
Order By: Relevance
“…13,18 However, a study conducted in United Arab Emirates showed that about half of the respondents had a history of fall in the past two years 4 and found significant association. 7,16 Similarly, present study found that the level of fall risk is statistically significant with age and vision problem (p=<0.05). Similar findings were found in the studies conducted in United State Emirates 4 , United State 9 , Saudi Arabia 7 , Brazil 12 and India 18,21 which showed that age is statistically significant.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…13,18 However, a study conducted in United Arab Emirates showed that about half of the respondents had a history of fall in the past two years 4 and found significant association. 7,16 Similarly, present study found that the level of fall risk is statistically significant with age and vision problem (p=<0.05). Similar findings were found in the studies conducted in United State Emirates 4 , United State 9 , Saudi Arabia 7 , Brazil 12 and India 18,21 which showed that age is statistically significant.…”
Section: Discussionsupporting
confidence: 71%
“…Likewise, the studies showed level of fall risk was statistically significant with vision problem. 16,21,22 Moreover, in present study, the level of fall risk was not significant with other variables such as sex, chronic diseases, urinary problems, use of assistive devices and taking number of medication (p=>0.05). However, other studies found that fall risks was significantly associated with sex 4,11,18,23 and chronic diseases.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations